Analysis of work ethics integrity and supervision on the performance of security units in outsourcing - Rafi Bajra Putra; Gendut Sukarno (Institute of Computer Science (IOCS), 2023)
This research aims to analyze work ethic, and integrity and supervise the performance of the service unit on outsourcing. This is quantitative research with the population in this study consisting of the security officers (Security Unit/Satpam) at PT. Karunia Adi Sentosa located in East Java with 45 personnels. The sampling technique used the Slovin formula, which amounted to 45 respondents. The data collection technique was through distributing questionnaires (surveys) to the security personnel. The questionnaire has been tested for validity and reliability tests. Analysis techniques used Partial Least Square (PLS) techniques. The results of the study show that work ethic have a significant positive impact on peformance, good integrity have a significant positive impact on peformance and control within the organization have a significant positive impact on performance.